Efecto de métodos de riego deficitario sobre el comportamiento fisiológico del cultivo de maíz (Zea mays) bajo condiciones climáticas de Manabí - Cevallos Morales, Teresa Nikole (2022)
The problems that most overwhelm humanity is the lack of water; which has motivated the creation of new irrigation technologies with the purpose of increasing the efficiency in the use of water and lower energy consumption. The objective of this research is to evaluate the physiological behavior of the DASS 3383 hybrid maize crop, under 3 deficit irrigation methods, a completely randomized block design (DBCA) was applied, performing 6 treatments with 4 repetitions each, T1: Treatment without deficit, T2: ORDI (Optimized Deficit Irrigation by Stages) 50% of irrigation needs (Nr), T3 ORDI 50% Nr + PRD 1 week, T4 ORDI 50% Nr + PRD 2 weeks, T5 ORDI 50% Nr 1 week , T6: ORDI 50% Nr 2 weeks; forming 24 experimental units, which evaluated the following variables: plant height, biomass (root, leaf and stem), stomatal conductance, humidity and water productivity; among the relevant results, it was obtained that T1 presented the highest average of: plant height (240.55 cm), stomatal conductance (220.58 µmol m2s-1) and higher volumetric water content in the soil profile; the methodology with Partial Root Drying (PRD) at 50%, for one week (T5), reached the highest water productivity with an average value of 59.75 Kg/mm; the deficit irrigation methods applied in treatments 6, 4 and 5 allowed to obtain the highest root biomass weight with values of 1.20, 1.18 and 1.08 g respectively.